Correction to: The role of recombinant LH in women with hypo-response to controlled ovarian stimulation: a systematic review and meta-analysis - Alessandro Conforti; Sandro C. Esteves; Francesca Di Rella; Ida Strina; Pasquale De Rosa; Alessia Fiorenza; Fulvio Zullo; Giuseppe De Placido; Carlo Alviggi (BMC, 2019)
.